Knowledge, Attitude and Practice Regarding Personal Protective Equipment During COVID–19 Pandemic Among Healthcare Workers in Hetauda - Bhattarai, Susmita; Pradhan, Srijana (Nepal Journal of Health Sciences, 2021)
Introduction: Personal protective equipment (PPE) is one of the effective measures to protect health care workers while caring confirmed or suspected patients with COVID-19. Objective: To assess the knowledge, attitude, and practice regarding the use of PPE among healthcare workers (HCWs) in Hetauda during COVID-19 pandemic. Methods: A descriptive cross-sectional study was conducted among 138 HCWs from three hospitals in Hetauda: Hetauda Hospital, Makwanpur Sahakari hospital and Hetauda Orthopedic Hospital between December 2020 and January 2021 for two weeks. A validated self-administered questionnaire, Likert scale and Observational checklist were used for data collection. The simple descriptive statistics (percentage, mean) and inferential statistics (Chi-square test) were used for the data analysis. Results: The findings of the study showed that the mean age of the respondents was 26.54 years. Half of the total respondents 70 (50.7%) had adequate knowledge, half 69 (50%) had positive attitude and more than half of the respondents had poor practice 60 (60%) regarding the use of PPE during COVID-19 pandemic. There was significant association of knowledge regarding the use of PPE with training, continue education, profession and attitude at p<0.05 level of significance. Conclusion: This study concludes that the periodic training program for newly recruited HCWs and refresher training/ continue education for old HCWs to update about the proper use of PPE would enhance the knowledge, attitude and practice of the HCWs. The hospitals should follow the standard PPE guidelines by CDC or WHO while donning and doffing the PPE during the care of Covid patients.